Resident Performed Sutureless Manual Small Incision Cataract Surgery (MSICS): Outcomes - Subudhi P (Dove Medical Press, 2021)
Praveen Subudhi,1 Sweta Patro,1 B Nageswar Rao Subudhi,1,2 Silla Sitaram,1 Zahiruddin Khan,2 Chandan Mekap1 1Cataract Department, Ruby Eye Hospital, Berhampur, Ganjam, Odisha, India; 2Ophthalmology Department, Hitech Medical College, Bhubaneswar, IndiaCorrespondence: Praveen SubudhiRuby Eye Hospital, Govinda Vihar, Sushruta Nagar, Berhampur, Ganjam, Odisha, 760001, IndiaEmail subudhipraveen@gmail.comPurpose: To show the surgical and visual outcomes of a resident-performed manual small incision cataract surgery.Study Type: Retrospective observational case series.Study Setting: Ruby Eye Hospital.Materials and Methods: Manual small incision cataract surgery was performed on 339 uncomplicated cataract cases by three in-house residents. Preoperative visual acuity and vision with a pinhole were meticulously noted in the record sheets. All patients underwent thorough preoperative evaluation with the help of a slit lamp. Eyes with corneal guttae, un-dilated pupils, pseudo-exfoliation, raised intraocular pressure and posterior segment abnormalities were excluded from the study. The mean patient age was 59 years (min: 47 years and max: 85 years). Forty-seven percent were males, and the rest were females. The mean uncorrected preoperative visual acuity recorded was 1.3 logMAR units (max: 1 and min: 1.6, Std dev: 0.4). Forty-two percent of the eyes had dense nuclear cataracts (≥ Nuclear Sclerosis grade III from LOCS II).Results: The mean postoperative visual acuity recorded was 0.4 logMAR units [standard deviation 0.3 logMAR units (max: 1 and min: 0.1 p-value < 0.001)]. Forty-three cases (12.6%) had tunnel-related complications (premature entry/button hole). Thirty-six cases (10.6%) had iatrogenic prolapse of the iris tissue. Eight cases (2.3%) had a runaway capsulorhexis, while 18 cases (5.3%) had iatrogenic posterior capsular rupture. Two cases (0.58%) had a large zonular dialysis. Ten cases (2.9%) were retaken to the operating room again for repeat intervention.Conclusion: The ophthalmic resident learning curve for manual small incision cataract surgery is steep, unlike what is reported in the literature. A good training program with a special emphasis on wound construction is of paramount importance for future residents.Keywords: MSICS, resident training, wound construction